Os poderes do juiz na Inglaterra e no Brasil: estudo comparado sobre os case management powers - Costa, Henrique Araújo (2012)
This text proposes a comparative study of English and Brazilian civil procedure. The research approaches the judge powers, specifically the case management powers. Considering the issue s delimitation, new statutes and its practice are compared through the perspective of both countries. In conclusion, these judge powers have become similar due to the blending practices seen among different law families, as well as between different countries of the same family. However despite the convergence towards strengthening these powers the problems to be solved by these countries have distinct roots. In England the cost problem is the biggest one, while in Brazil the biggest problem is the delay. Moreover, despite their early convergence, the cultural roots of each system keep them somehow apart from one another. Thus it is not possible to state which would the best system (since they are unique) and the adoption of the English model by the Brazilian legislation should be done with caution (since the problems to be solved are different)